Prevalence of adenomyosis and associated gynaecological pathologies in hysterectomy samples: a retrospective study - Gopinath, Lekshminath; Vaidya, Rajani (International Journal of Research in Medical Sciences, 2021)
Background: Adenomyosis is a prevalent gynaecological disorder among women and it is a major cause for AUB. Its diagnosis is confirmed by histological examination of hysterectomized samples. Moreover it is associated with other benign gynaecological pathologies. The aim of this study is to identify the prevalence of Adenomyosis and its association with other benign gynaec pathologies in hysterectomized samples. Methods: This retrospective of two year duration was conducted in obstetrics and Gynaecology department of Malabar Medical College Hospital and Research Centre, a tertiary care centre in Kozhikode, Kerala from 2019 June to 2021 June. 452 patients underwent hysterectomy for abnormal uterine bleeding during this period. Among this, 76 patients had histologically proven adenomyosis in hysterectomy specimen and their case record were reviewed and the data was analysed. Results: The prevalence of Adenomyosis in this study was 16.8%. Majority of women were in age group of 41 to 46 (36.8%), followed by 46 to 50 age group (26.3%). 94 % of women were multipara with majority in para2 and para3 group. Only 6 % of women were nulliparous. Most common symptom was abnormal uterine bleeding (92%), followed by dysmenorrhoea and chronic pelvic pain. Majority had overlap of symptoms. 7% of women were asymptomatic. In 60 % of women no other gynaec pathologies were identified. Most common associated pathology was leiomyoma (15.8%), closely followed by endometriosis (13.2%). Endometrial hyperplasia was associated with adenomyosis in 3.9%of women and endometrial polyp in 2.6%. Ovarian pathologies identified were simple ovarian cyst (2.6%) and serous cystadenoma (1.3%). Conclusions: In the present study, the prevalence of adenomyosis was high and abnormal uterine bleeding was the patients’ most prevalent complaint. Among the associated gynaec pathologies, leiomyoma had the highest correlation with adenomyosis.